2013
DOI: 10.1542/peds.2013-0909
|View full text |Cite
|
Sign up to set email alerts
|

Nurse and Physician Agreement in the Assessment of Minor Blunt Head Trauma

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Effective implementation of Pediatric Emergency Care Applied Research Network head trauma rules depends on their early application. As the registered nurse (RN) is often the first to evaluate children with blunt head trauma, initial RN assessments will be an important component of this strategy. WHAT THIS STUDY ADDS:We demonstrated fair to moderate agreement between RN and physician providers in the application of the Pediatric Emergency Care Applied Research Network head trauma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…The strategy of using nurses to collect these data must be weighed against the modest interobserver reliability between nurses and physicians for some clinical findings. 30 Experts continue to call for additional study to test the benefits of different workflows and features of EHR-based CDS (eg, requiring clinicians to justify overriding advice). 18,19,31,32 As in previous studies, we found that the PECARN TBI prediction rules accurately identified patients with ciTBI.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of using nurses to collect these data must be weighed against the modest interobserver reliability between nurses and physicians for some clinical findings. 30 Experts continue to call for additional study to test the benefits of different workflows and features of EHR-based CDS (eg, requiring clinicians to justify overriding advice). 18,19,31,32 As in previous studies, we found that the PECARN TBI prediction rules accurately identified patients with ciTBI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of interrater agreement have focused on physician-physician or physician-nurse dyads. [26][27][28] We demonstrated that the overall percentage agreement was high for all modified Centor score predictors between the clinician and patient or parent. When we evaluated the κ, however, which measures agreement beyond chance alone, the agreement for historical symptoms was moderate or high and lower for clinical examination findings.…”
Section: Figurementioning
confidence: 99%
“…El grado de conformidad entre el personal de enfermería y los facultativos médicos para la aplicación de las múltiples guías de TCEL pediátrico es moderado en niños mayores y algo inferior en lactantes (187). Así como la aceptación de los clínicos con las guias de practica clínica es elevada teniendo en cuenta que se debe individualizar cada caso ya que no todos los pacientes pueden ser incluídos en los algoritmos propuestos (108).…”
Section: Variabilidad En El Manejo Del Tcelunclassified